The Association Between Plasma Hyaluronan Level and Plaque Types in ST-Segment–Elevation Myocardial Infarction Patients - Li, Jiannan; Tan, Yu; Sheng, Zhaoxue; Zhou, Peng; Liu, Chen; Zhao, Hanjun; Song, Li; Zhou, Jinying; Chen, Runzhen; Chen, Yi; Yan, Hongbing (Frontiers in Cardiovascular Medicine, 2021)
Background: The metabolism of hyaluronan (HA) is widely known to be involved in the process of acute coronary syndrome, but it is unknown how circulating HA levels change in ST-Segment–Elevation Myocardial Infarction (STEMI) patients and whether HA is associated with plaque morphology, including rupture and erosion. Objectives: This study focused on the changes in the plasma levels of high molecular weight (HMW) HA (>35 kDa) and CD44 in STEMI patients and their relationship with plaque morphology evaluated by optical coherence tomography (OCT). Methods: We prospectively enrolled 3 cohorts in this study, including 162 patients with STEMI, 34 patients with stable coronary artery disease (S-CAD) and 50 healthy controls. Plaque morphology was detected by OCT analysis, and the plasma levels of HMW HA and CD44 were examined by enzyme-linked immunosorbent assay (ELISA). We compared plasma level of HMW HA and CD44 among STEMI patients, S-CAD patients and healthy controls, as well as in plaque rupture and plaque erosion. Results: The plasma levels of HMW HA and CD44 were significantly lower in STEMI patients than in healthy controls (p=0.009 and p<0.001, respectively). In addition, plasma level of HMW HA in plaque erosion was significantly lower than that in plaque rupture (p=0.021), whereas no differences were found in plasma level of soluble CD44 between plaque rupture and erosion. Conclusions: Low levels of circulating HMW HA and CD44 were independently correlated with STEMI, and low levels of HMW HA were associated with plaque erosion compared with rupture. Moreover, plasma HMW HA might be a useful biomarker for identifying plaque erosion to improve the risk stratification and management of STEMI patients.